2006
DOI: 10.1158/0008-5472.can-06-1886
|View full text |Cite
|
Sign up to set email alerts
|

HBXIP, Cellular Target of Hepatitis B Virus Oncoprotein, Is a Regulator of Centrosome Dynamics and Cytokinesis

Abstract: Hepatitis B virus accounts for more than 1 million cancer deaths annually, but the mechanism by which this virus promotes hepatocellular carcinoma remains unclear. The hepatitis B virus genome encodes an oncoprotein, HBx, which binds various cellular proteins including HBXIP. We show here that HBXIP is a regulator of centrosome duplication, required for bipolar spindle formation in HeLa human carcinoma cells and primary mouse embryonic fibroblast cells. We found that most cells deficient in HBXIP arrest in pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 31 publications
3
68
0
3
Order By: Relevance
“…These results were consistent with previous findings that the HBV X protein is associated with cell cycle checkpoint controls [Fujii et al, 2006b]. Based on proteomic findings, several key steps in the cell cycles are likely to be affected by HBV replication and protein expression.…”
Section: Discussionsupporting
confidence: 93%
“…These results were consistent with previous findings that the HBV X protein is associated with cell cycle checkpoint controls [Fujii et al, 2006b]. Based on proteomic findings, several key steps in the cell cycles are likely to be affected by HBV replication and protein expression.…”
Section: Discussionsupporting
confidence: 93%
“…The hBubR1 siRNA duplex significantly reduced BubR1 expression in ChangX cells (Figure 2d) and we found that the kinetochore localization of HBx was diminished in cells lacking kinetochore hBubR1 (Figure 2b, lower panel). In contrast, centrosomal localization of HBx (Fujii et al, 2006) appeared not to be affected by BubR1 siRNA (Figure 2b, arrows). Localization of CDC20 to kinetochores appeared to be stable in cells depleted of BubR1 (data not shown).…”
Section: Hbv X Targets Hbubr1 S Kim Et Almentioning
confidence: 91%
“…This is likely associated, at least in part, with the observation that integration of the HBV genome causes rearrangement of cellular DNA (Henderson et al, 1988). In addition, our group and others have observed that the HBV X protein (HBx) viral oncoprotein is directly involved in hyperamplification of centrosomes, which leads to chromosome aberrations (Forgues et al, 2003;Yun et al, 2004;Fujii et al, 2006).…”
Section: Introductionmentioning
confidence: 88%
“…Interestingly, growing evidence shows that HBXIP has broad roles in cancers. HBXIP can suppress apoptosis through survivin/caspase 9 in hepatoma cells (2) and regulates centrosome duplication, causing excessive centrosome production and multipolar mitotic spindles in HeLa cells (3,4). It has been reported that HBXIP is a component of Ragulator, which is a guanine nucleotide exchange factor (GEF) for the Rag GTPases that signal amino acid levels to mTORC1 (5).…”
Section: Hepatitis B X-interacting Protein (Hbxip)mentioning
confidence: 99%